National Curriculum Collaboration The State of Reform in the States and Territories - Watt, Michael G. ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
Between 1986 and 1993 Australia developed a national curriculum framework of statements and profiles in eight learning areas. These areas were (1) English, (2) mathematics, (3) science, (4) studies of society and the environment, (5) arts, (6) health and physical education, (7) technology, and (8) languages other than English. This development represented the most significant curriculum reform ever attempted in Australian education. Previous studies have examined the effects of the contrasting doctrines of corporate federalism and economic reform with the states' rights' position adopted by the states and territories. This article explores how antecedent conditions for curriculum development have influenced the process of implementing the national statements and profiles in the states and territories between 1993 and 1997. The states and territories examined are Queensland, New South Wales, Victoria, South Australia, Western Australia, Tasmania, Australian Capital Territory, and the Northern Territory. The national curriculum reform movement was based on assumptions and goals driving the broader agenda for educational reform during the 1980s. The individual states and territories, however, had already begun their own curricular reforms by the time the national agenda began implementation in the 1990s. The level of success and implementation of the national curriculum has been significantly affected by the success, degree of political support, and level of implementation of the individual efforts in each state and territory. (MJP)
ERIC Note: Paper presented at the Biannual Meeting of the Australian Curriculum Studies Association (Sydney, New South Wales, Australia, 10-13 July, 1997).
Administrators.
Practitioners.
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Curriculum Design; Curriculum Development; Educational Change; Educational Cooperation; Educational Legislation; Educational Planning; Educational Policy; Educational Quality; Elementary Secondary Education; Foreign Countries; National Programs; State Standards; Student Evaluation; Australia; Reports, Descriptive; Speeches/Meeting Papers